Analisis Pengaruh Kualitas Kinerja Karyawan terhadap Tingkat Kepuasan Pelanggan di Toko Anty Shop28 di Makassar - Pattola, Femina; Baharuddin, Baharuddin; Sambara, Kordiana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the effect of employee performance quality on customer satisfaction at Anty Shop28 Cosmetics in Makassar. The research employs a quantitative approach using primary data collected through questionnaires distributed to 91 respondents who are customers of Anty Shop28 Cosmetics. The independent variable in this study is employee performance quality, while the dependent variable is customer satisfaction. Data were analyzed using Pearson correlation analysis, coefficient of determination, and partial hypothesis testing (t-test). The results indicate that employee performance quality has a positive and significant effect on customer satisfaction. This is evidenced by a significance value of 0.001, which is lower than the significance level of 0.05. The Adjusted R Square value of 0.711 suggests that 71.1% of the variation in customer satisfaction is explained by employee performance quality, while the remaining 28.9% is influenced by other factors not examined in this study. Furthermore, the t-test results show a t-value of 14.688, which exceeds the t-table value of 1.961, indicating that the proposed hypothesis is accepted. In conclusion, higher employee performance quality leads to higher levels of customer satisfaction. This study recommends that Anty Shop28 Cosmetics continuously improve employee performance through service training, discipline, effective communication, and accuracy in order to enhance customer satisfaction and maintain competitiveness in the cosmetic retail industry.